The Monitoring Chicken Cage Based on Wireless Sensor Network and Internet of Things - Fahmi, Nurul; Riyanti, Agus (Politeknik Negeri Banyuwangi Jl. Raya Jember km. 13 Labanasem, Kabat, Banyuwangi, Jawa Timur (68461) Telp. (0333) 636780, 2022)
The Farming is a business that is growing very rapidly and has a high enough demand, especially raising poultry such as broilers. Poultry farming includes all processes of raising poultry for food purposes, namely broilers. Most Indonesian people, especially in the area of Sumatra Island, Riau Province in Bengkalis Regency, raising broiler chickens does not really pay attention to the conditions of temperature and humidity. So, that body growth is slower and health is less guaranteed. This results in chickens that are not producing meat as usual. From the problem above, in this paper proposed a system Smart Chicken Cage where can monitoring chicken cage using sensor temperature and humidity. The system generally consists of two sensors such as temperature LM35 and humidity DHT22. Arduino uno used as micro-controller to collect data chicken cage from sensor used. Raspberry Pi as gateway for the saving data temperature and humidity to database MySQL. Communication from Arduino to gateway used Wireless Sensor Network (WSN) with protocol Xbee 802.15.4 and to connect to cloud used Internet of Things (IoT) technology. Furthermore, all sensor data sensor will display to process and testing analysis. So, chicken farmer can be monitoring chicken cage use web-based application, Android Application.